The Quest for Equilibrium: Navigating Hybrid Logics in Indonesian Islamic Microfinance Bank (BPRS). - Akbar, Taufik (KEUNIS, 2025)
This research explore the unique hybrid logic that defines BPRS, institutions navigating the complex interplay of market, social, religious, and accountability logics. These logics, encompassing both material and symbolic aspects, are interconnected yet analytically distinct, offering nuanced perspectives on the dynamics within Islamic microfinance. Adopting a qualitative approach, this study focuses on two BPRS institutions, strategically selected to represent rural (R) and urban (U) contexts. Data was gathered through interviews with key personnel, including board members, Shariah Supervisory Board members, and branch heads, totaling nine (9) respondents. The findings reveal that market logic drives profit generation and the development of Shariah-compliant products, while social logic shapes customer selection and community development initiatives. Religious logic influences all material facets, from product structuring to customer relationships. Accountability logic encompasses regulatory compliance, ethical responsibility, and a divine dimension. This hybrid logic framework elucidates the paradoxical practices observed in Islamic microfinance, such as balancing profit with social impact and religious compliance with market competitiveness. Ultimately, this research contributes to a deeper understanding of the institutional environment of Islamic microfinance, where organizations negotiate competing demands to achieve financial sustainability, social welfare, religious adherence, and accountability.